2001
DOI: 10.7863/jum.2001.20.8.829
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative evaluation of pelvic tumors by Doppler and three‐dimensional sonography.

Abstract: Objective. To study a spectrum of systems (two-dimensional transvaginal, transvaginal color Doppler, three-dimensional, three-dimensional power Doppler, and contrast-enhanced three-dimensional power Doppler sonography) for preoperative evaluation of pelvic tumors. Methods. Two hundred ninety-two patients were evaluated by the 5 complementary methods in preoperative sonographic assessments. We examined adnexal and endometrial morphology, thickness, and volume by two-and three-dimensional sonography and analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 25 publications
2
43
0
2
Order By: Relevance
“…16 Some researchers have evaluated the role of 3D sonography for discriminating between benign and malignant adnexal masses. Bonilla-Musoles and colleagues 5 and Kurjak and coworkers 6 found that 3D sonography was more sensitive than 2D sonography. Conversely, Hata and coworkers 7 found that 3D sonography was more specific than 2D sonography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Some researchers have evaluated the role of 3D sonography for discriminating between benign and malignant adnexal masses. Bonilla-Musoles and colleagues 5 and Kurjak and coworkers 6 found that 3D sonography was more sensitive than 2D sonography. Conversely, Hata and coworkers 7 found that 3D sonography was more specific than 2D sonography.…”
Section: Discussionmentioning
confidence: 99%
“…4 Several studies have evaluated the role of 3D transvaginal sonography in assessing adnexal masses, reporting controversial results. [5][6][7][8] The issue of reproducibility is essential when proposing a new technique to be introduced into clinical practice. The objective of this study was to evaluate the reproducibility of 3D sonographic morphologic assessment of adnexal masses.…”
mentioning
confidence: 99%
“…13 More recently, evidence has become available showing the advantages of 3D sonography in gynecology. In these studies, 3D sonography allowed improved classification of ovarian tumors 14 as well as improved evaluation of the postmenopausal endometrium. 15,16 Finally, 3D sonography was highly accurate in the diagnosis of müllerian anomalies.…”
mentioning
confidence: 99%
“…They found 3D US more sensitive than 2D US (87% versus 80%) with similar specificity (96% and 95%, respectively). 21 We found that 3D ultrasonography had not statistically better diagnostic performance than 2D in a series of 44 selected complex adnexal masses. 22 In our study one examiner performed 2D examination and another the 3D examination.…”
Section: Static Three-dimensional Ultrasoundmentioning
confidence: 85%